THE RELATIONSHIP BETWEEN STUNTING AND STUDENT LEARNING ACHIEVEMENT IN ELEMENTARY SCHOOL/MINISTRY IN THE WORKING AREA OF LIGAN PUSKESMAS, ACEH JAYA DISTRICT - Ambia Nurdin; Fauzan; Muhammad; Zamzami; Bukhari; Murtadhahadi; Mohd Isa T.Ibrahim; Mulyadi; Zahrul Fuadi; Mahyuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The incidence of stunting (short) under five is a major nutritional problem in all countries. Based on three years of nutritional status monitoring (PSG) data, stunting in Indonesia shows that stunting has the highest prevalence compared to other nutritional problems such as malnutrition, wasting, and obesity. This is due to the pregnancy process of mothers who experience malnutrition during pregnancy, low Early Breastfeeding Initiation (IMD), and inadequate provision of MP-ASI. This study aims to determine the relationship between stunting and student achievement in SD/MIN schools in the work area of ​​the Ligan Health Center, Aceh Jaya Regency. This study uses a type of quantitative research. The population of this study were all SD/MIN students in the working area of ​​the Ligan Health Center, Aceh Jaya Regency in 2022. The respondents used were students aged 7-12 years and had complete report cards. Researchers took samples using the consecutive sampling method. The samples obtained were 49 samples from different schools. This research was conducted in 3 schools in the working area of ​​SD/MIN Puskesmas Ligan, Aceh Jaya Regency. There were 18 children from SD 12, 15 children from SD 2 and 17 children from MIN 8. The statistical test analysis used the Chi-Square Test, while the student measurements used a meter, then plotted onto the CDC-2000 curve to see TB according to age. The research results obtained 49 students as respondents. The average respondent was found at the age of 7 years (30.6%), and the least was found at the age of 12 years (6%). The results of the analysis test showed that there was no significant relationship between stunting and learning achievement (0.452 > 0.05). Conclusion: There is no significant relationship between stunting and student achievement.